Pendidikan Akhlak Remaja Keluarga Muslim di Era Industri 4.0 - Partono (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2020)
The purpose of this study was to determine the role of parents and strategies in improving moral education in adolescents in Muslim families in the industrial era 4.0. The focus of this research problem is on how the concept of the role and strategies of adolescent moral education carried out by Muslim families in the industrial era 4.0. This type of research is a qualitative research with a descriptive qualitative approach. The results showed that parents' understanding of adolescent moral education is still very lacking, parental understanding of Islamic religion is still minimal so that adolescent ahklaq education in Muslim households or families is very limited and the concept of family education for adolescents in moral education is to provide role models and provide knowledge of intolerance to individual teenagers at home.